Validation of Developed Instruments on Study Habits, Creativity, and Self Concept on College Students in Nigeria - Adamu Mayanchi, Sulaiman; Khan, Aqeel; Binti Abdul Latif, Adibah (International Journal of Psychosocial Rehabilitation, 2020)
The role of validating a questionnaire is to ensure that the questionnaires for use in research settings are psychometrically sound, valid, and reliable, as well as efficient and effective. This article will therefore provide the validation of existing resources on study habits, creativity, and self-concept through the use of the Rasch Measurement approach. A pilot study was randomly selected from each of the two colleges in Zamfara State, with a sample of 180 respondents. The employed Rasch-based Winsteps code produces the required parameter estimate automatically. The results of the reliability coefficients showed the reliability of 0.83, 0.96, and 0.87 items, with 0.96, 0.91, and 0.94 corresponding to Cronbach's alpha. The unidimensional construct of the test measures supported by the raw variance explained by measurements of 48.3 percent, 53.8 percent, and 53.0 percent closely match the variance expected. Investigation of the map of the item person revealed that all items fell within the respondents ' ability level. Likewise, fitness indices showed that 5 items were listed to delete items for study habits, and subscale creativity reveals that all 23 items in the scale have reasonable fitness, while 5 items have poor self-concept subscale fitness indices. The results confirm the accuracy of the explanations and inferences of the scores on the objects and subscales of the instruments.